STANDARDIZING THE ANNUAL ELECTRIC ENERGY CONSUMPTION FOR A RESIDENTIAL BUILDING IN BASRAH CITY - Almudhaffar, Mujtaba; Monem, Ali A.; Naseer, Ahmed H. (Basrah Journal for Engineering Sciences, 2014)
The present work is aimed to reduce the annual electric energy consumption in a residential building in Basrah city through introducing a standardized rule for the annual electrical consumption for the cooling and heating purposes. This work will concentrate on all parameters which help to go toward the optimum use of thermally efficient house. The building energy analysis program e-Quest was used to simulate the annual energy consumption for a typical residential house built with different types of building materials. Transfer function cooling load calculation was used. The results showed that for the Base- House, the thermal transmission through the walls and roof constitutes more than half of the total peak cooling load. It was found that a house built with thermo-stone causes 5.9% reduction of the annual cooling energy consumption, and 12.4% in the annual heating energy consumption. However, insulating the Base- House causes a significant reduction in the air conditioning equipment capacity and consequently reduction in cooling energy consumption by 23%, and reduces the heating energy consumption by 42.8%. Finally this work presents a useful planning to developed building design which reduces the electrical energy consumption.